Mobility of exogenous lead in acidic soil treated with wheat straw biochar after aging process of freeze-thaw cycles. Issue 1 (31st December 2022) - Mo, Huijing; Wang, Lei; Wang, Yu; Zhang, Lianyi; Gu, Xinfeng; Ding, Zhuhong
ABSTRACT: Although biochar has been investigated extensively to stabilize soil heavy metals, there were limited investigation on the stabilization of soil heavy metals by using biochar under the natural ageing processes of alternate-cooling/heating. In this study, wheat-straw-biochar-treated soil samples contaminated with Pb(II) ions/PbO were subjected to 12 h-freeze/12 h-thaw cycles simulating the natural alternate-cooling/heating process. After the freeze-thaw process, the mobile fractions of leadreduced by 30.0% (500 mg·kg −1 Pb(II) spiked soil) and 19.5% (PbO spiked soil) due to biochar's addition evaluating via 0.01 M HCl batch extraction. Compared with the control, the mobile Pb in treated groups decreased in column leaching . Exchangeable lead decreased by 6.4% – 80.9% due to biochar addition. Freeze-thaw ageing had no significant effects on lower lead leaching and lower exchangeable lead resulted from biochar's addition. Therefore, wheat-straw-biochar treatment is helpful for stabilization of both dissolved Pb and particulate Pb in soil under the alternate-cooling/heating ageing process.